Water pipeline leakage detection using vibration method - Hazwan Azhar Tahwil Azar, 1987- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Thesis (Sarjana Sains (Kejuruteraan Sistem Komputer)) - Universiti Teknologi Malaysia, 2014